Allergen-specific circulating CLA+ memory T cells stratify IL-22 response in atopic dermatitis skin - Irene García-Jiménez; Irene García-Jiménez; Lídia Sans-de San Nicolàs; Sandra Díez-Ribas; Laia Curto-Barredo; Marta Bertolín-Colilla; Ana Vivancos-Melenchón; Ignasi Figueras-Nart; Montserrat Bonfill-Ortí; Anna Ryzhkova; Marta Ferran; Tali Czarnowicki; et al. (Frontiers in Immunology)
BackgroundCurrent understanding of IL-22 in atopic dermatitis (AD) mostly relies on animal models, intracellular staining of polyclonally activated peripheral lymphocytes, and biological therapies.MethodsWe evaluated the IL-22 response to house dust mite (HDM) extract in 58 patients with moderate-to-severe AD using a coculture system made of circulating memory cutaneous lymphocyte associated antigen (CLA)+/− T cells with autologous lesional epidermal cells. Additionally, we performed histological and gene expression analysis in lesional skin biopsies, assessed specific IgE levels in plasma, and together with the clinical features of the patients, were related to the IL-22 in vitro response.ResultsHDM triggered heterogeneous IL-22 secretion in memory T cells, preferentially in the CLA+ subset, which enabled patient stratification into IL22 producers (IL22P, n=17) and non-producers (IL22NP, n=41). IL22P showed an increased degree of epidermal thickness, overexpression of IL22 in lesional skin areas, elevated specific IgE levels against HDM and SEB in plasma, and a higher proinflammatory profile compared to IL22NP.ConclusionsThis is the first report showing that allergen-specific CLA+ T-cell-mediated IL-22 in vitro response functionally distinguish moderate-to-severe adult AD patients with specific clinical features and activated IL-22 pathway in their lesional skin, paving the way for the selection of patients that may benefit from IL-22-directed therapies.